Importance of demographic characteristics and nurses' role in women's perceptions and experiences of gynaecological examination - Zaić, Dušanka (Obzornik zdravstvene nege, 2015)
Introduction: Gynaecological examination is crucial for protecting the reproductive health of women. The purpose of the study was to explore the perception of women towards gynaecological examination, the importance of some demographic characteristics and the role of a nurse. Methods: A quantitative methodology was used for study purposes. A structured web questionnaire was applied on a non-random, convenience sample of women (n = 476). The questionnaire was published on the most popular Slovenian web forums. Prior to the main research project, a pilot study was conducted on a sample of 10 women. The statistical analysis included descriptive statistics, t-test, Pearson's and Spearman's correlation coefficient. Results: Results of the study show a statistically significant correlation between the respondents' residential environment (t = -2.436, p = 0.015), the level of educational attainment (rs=-0.153, p = 0.001) and the presence of discomfort and fear before the gynaecological examination. The role of a nurse in reducing the level of discomfort and fear before (t = -0.931, p = 0.352) and during (t = -0.888, p = 0.375) the gynaecological examination was not proven statistically significant. Discussion and conclusions: Besides the demographic characteristics, a number of personal and societal factors influence women's attitudes towards gynaecological examination and the associated discomfort and fear. The study suggests that further qualitative studies are needed to gain a deeper understanding of how women experience a pelvic examination.
Keywords: empathy; empatija; ginekologija; gynecology; nursing care; patients' rights; pravice pacientov; reproductive health; reproduktivno zdravje; zdravstvena nega